Journals and correspondence from the New Hebrides - Paton, Maggie Whitecross, 1841?-1905.; Australian National University. Pacific Manuscripts Bureau (1870)
The collection comprises the journal, September 1870-March 1872; journal, February 1874-November 1875; and, correspondence from Minnie Paton to William (Wilfred) Paton, October 1942, including "some of Fred's jokes" and small excerpts transcribed from Maggie Whitecross' journals.
Microfilm.
Microfilm copy of originals held in private ownership.
Margaret (Maggie) Whitecross was born in about 1841 and, in 1864, became the second wife of Presbyterian missionary, the Reverend John Gibson Paton (1824-1907). Reverend John G. Paton and Maggie Paton travelled from Scotland to the New Hebrides in August 1866 and established a Mission station on Aniwa Island, near to Tanna. Maggie Paton bore ten children, four of whom died. Two sons, Frank Hume Lyall Paton and Frederick James Paton, later followed as missionaries in the New Hebrides. Reverend Paton learned the local language and translated the New Testament into the Aniwan language. Maggie Paton taught women and girls craft, singing and reading.
Together they translated, printed and taught the Scriptures, ministered to the sick and dying, taught the practical use of tools, held worship services and trained native teachers who were later sent to the villages to preach the gospel. Maggie Paton's Letters and sketches from the New Hebrides was edited by her brother-in-law, the Reverend Jas. Paton, and published in 1895. Maggie Paton died at Kew, Victoria in 1905 at the age of 64.
Keywords: Paton, Maggie Whitecross, -- 1841?-1905 -- Archives; Missionaries' spouses -- Scotland -- Archives; Missionaries' spouses -- Vanuatu -- Archives; Presbyterian Church -- Missions -- Vanuatu; Ni-Vanuatu -- Missions; Vanuatu -- Religion; Missionaries; Spouses